FORMATION OF MATHEMATICAL LITERACY OF PRIMARY SCHOOL STUDENTS THROUGH INTEGRATION - Zakiya Akhmedovna Narimbetova (Web of Journals Publishing, 2024)
This article describes the development of mathematical literacy of primary school students through extracurricular activities and their interests.
Keywords: Mathematics, method, mathematical concepts, communication, volume, pedagogy, teaching, culture.